Assessment of Sensitivity and Specificity of CEA in Primary Diagnosis of patients with Gastrointestinal Malignancy - Khan, Saiful Islam; Md Shafiqul Islam; Quazi Mehranuddin Ahmed; Mostak Ahmed; Md Sidur Rahman Mollah; Sharif Jayad Atique; Md Tofazzal Hussain; Rifat Subrina Anna; ASM Tanjilur Rahman; Ratan Kumar Saha (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Primary Diagnosis of GI (gastrointestinal) malignancy is difficult and most of the diagnostic tools were costly and invasive. The clinical validity of monitoring the serum biomarker carcinoembryonic antigen (CEA) was assessed in 100 patients with gastric, duodenal and colorectal adenocarcinomas in a tertiary-level hospital in Bangladesh. Sensitivity and specificity of the test were evaluated preoperatively. Patients were assessed clinically, radiologically, and biochemically. Our study revealed that in gastrointestinal (GI) malignancy as a whole the CEA test had a preoperative sensitivity and specificity of 54% and 80%, respectively. In stomach cancer, the sensitivity and specificity of CEA were 33.33% and 100%, respectively. In duodenal adenocarcinoma and carcinoma of caecum, the sensitivity and specificity of CEA were 66.67% and 40.0%, respectively. In colonic cancer, the sensitivity and specificity of CEA were 42.86% and 60.0%, respectively. In rectal carcinoma, the sensitivity and specificity of CEA were 42.86% and 63.64%, respectively. All these values are not statistically significant. So for detecting GI malignancies, the use of CEA is not widely recommended due to its low sensitivity and high specificity. An additional finding was that serum CEA levels were significantly elevated in advanced stages of gastrointestinal (GI) malignancy, with the highest levels observed in stage D (100%) followed by stage C (92.3%) and stage B (32.3%). Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):70-73